IMPROVING STUDENTS’ VOCABULARY BY USING COMIC STRIPS IN TEACHING NARRATIVE TEXT - Budiman, Petrus Gito; Sada, Clarry; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research was done to investigate the use of comic strips to improve the students? vocabulary in teaching narrative text. The form of this research is a classroom action research, in which the subject is the eight grade students of SMPN 2 Putussibau in academic year 2017/2018. The subjects of this research were 24 students in VIII B. The data were collected from the students? score in test, observation checklist, and field notes. The students? achievement towards the learning process was gathered by observation checklist and field note. The data of vocabulary mastery was obtained by the test. Based on data, the students showed improvement in the teaching process. There were two cycles in conducting this research. In the first cycle, the students? mean score was 59,79. The result were classified as ?poor? level. In the second cycle, the students? mean score was 78, 75. The result was classified as ?Average? level. The students were easier in understanding the meaning of the new vocabulary, and also the students are easier in understanding the text. The students? vocabulary of the eighth grade students of class VIII B of SMPN 2 Putussibau in academic year 2017/2018 improved by using comic strips in teaching narrative text.Keywords : Improving, Vocabulary, Comic Strips.